PENGARUH MODEL PEMBELAJARAN RMS TERHADAP KEMAMPUAN BERPIKIR ALJABAR DITINJAU DARI KEMAMPUAN PENALARAN MATEMATIS - Arie Purwa Kusuma; Nurina Kurniasari Rahmawati; Lamanda Ayuningrum (Universitas Pekalongan, 2022)
The purpose of this study was to determine the effect of using the Reading Mind Mapping and Sharing (RMS) learning model and direct learning model on algebraic thinking skills in terms of students' mathematical reasoning abilities. This type of research is a quasi-experimental research population, namely the students of SMPN 2 Solear. Sampling was done by using the cluster random sampling technique and the research sample was 70 students. The instruments used in data collection are algebraic thinking ability tests and mathematical reasoning tests. Data prerequisite test includes normality test using Lilliefors test and homogeneity test using Fisher and Bartlett test with = 0.05, concluded that the sample is normally distributed and homogeneous. Hypothesis testing using two-way analysis of variance with unequal cells. The results showed that there was no difference in algebraic thinking skills between the RMS model and the direct learning model and students with high mathematical reasoning abilities had better algebraic thinking abilities than students with moderate and low mathematical reasoning abilities, and students with moderate mathematical abilities had the same algebraic thinking abilities. good with students with low mathematical reasoning ability